2017
DOI: 10.1021/acs.iecr.7b02002
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Behavior of Some Motor and Gear-Boxes Oils at High Pressure: Compressibility Estimation at EHL Conditions

Abstract: Characterization of elastohydrodynamic lubrication, EHL, contacts requires an appropriate EoS for the lubricant. Experimental viscosities and speeds of sound of six lubricants from 278.15 to 398.15 K at 0.1 MPa together with densities up to 120 MPa are reported. Tammann-Tait and the two EoSs based on the scaling concept describe the experimental densities of the six oils with average deviations lower to 0.03%. Dowson-Higginson and Zhu and Wen equations currently used in numerical simulations of the EHL regime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Across all temperatures and pressures, the compressibilities are in the order PAO 8 ≈ PAO 4 > IIIA > IIIB > IIA > IIB with the differences between IIIB, IIA, and IIB being low. While the calculated compressibilities are higher than those reported by Guimarey et al, the trend of oil order appears to be in agreement, with a poly­(α-olefin), PAO 6, having higher values for compressibility than the reference group III oil used in that work. The discrepancies in values for compressibility may be due to the method of calculation: this work calculated values from an equation of state, while Guimarey et al calculated their values from density and speed of sound measurements …”
Section: Results and Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Across all temperatures and pressures, the compressibilities are in the order PAO 8 ≈ PAO 4 > IIIA > IIIB > IIA > IIB with the differences between IIIB, IIA, and IIB being low. While the calculated compressibilities are higher than those reported by Guimarey et al, the trend of oil order appears to be in agreement, with a poly­(α-olefin), PAO 6, having higher values for compressibility than the reference group III oil used in that work. The discrepancies in values for compressibility may be due to the method of calculation: this work calculated values from an equation of state, while Guimarey et al calculated their values from density and speed of sound measurements …”
Section: Results and Discussionsupporting
confidence: 71%
“…While the calculated compressibilities are higher than those reported by Guimarey et al, the trend of oil order appears to be in agreement, with a poly­(α-olefin), PAO 6, having higher values for compressibility than the reference group III oil used in that work. The discrepancies in values for compressibility may be due to the method of calculation: this work calculated values from an equation of state, while Guimarey et al calculated their values from density and speed of sound measurements Figure shows the comparison of isothermal compressibilities for all six oils at both 323 and 373 K. When the comparison is made between oils and their compositions, specifically cycloparaffin content, are taken into account, it can be seen that compressibility appears to drop as the concentration of cyclic compounds in the oil increases.…”
Section: Results and Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…To the authors’ best knowledge, experimental densities can be found for lubricants which have been measured up to pressures of 1 GPa and temperatures of 533 K. , With respect to the experimental methods of the time, the density data are necessary for calculating viscosities with increasing temperature and pressure. Instrumentation for measuring fluid expansion with changing pressures have included methods such as vibrating tube densitometers, specially designed piezometers, , and flexible bellows. The practical application of these density properties and their related thermal properties are needed to produce heat-transfer models for engine coolants and to maximize the transmitting pressure of hydraulic fluids. Other temperature-dependent properties that are derived using densities include the thermal pressure coefficient, γ; the internal pressure, p int ; the difference between specific isobaric heat capacity, c p ; specific isochoric heat capacity, c v ; thermal diffusivity, λ; dynamic viscosity, η; and Reynolds number, Re.…”
Section: Introductionmentioning
confidence: 99%
“…The common density prediction models typically follow the analytical Tait-Tamman Model and modified versions fit isotherms, with some versions able to fit temperature-dependent data. Other predictive models that include temperature dependence are the perturbed-chain statistical associating fluids theory (PC-SAFT), power law density scaling, general density scaling, Dawson–Higginson, Zhu–Wen, and Jacobson–Vinet. ,, The literature values for the temperature dependence of the densities for different vegetable oils have been measured and predicted using the Rackett equation using a priori knowledge of oil composition and the critical properties of the pure oils . These equations of state range from relatively simple to complex with many parameters with large data sets and require a large amount of temperature-dependent data to optimize.…”
Section: Introductionmentioning
confidence: 99%